Kinetic study into the phosphorus release and carbon conversion behavior of sewage sludge coke during gasification - Eric Franke; Sergei Shalnev; Felix Küster; Martin Gräbner (Chemical Engineering Journal Advances)
Sewage sludge (SS) is a promising secondary resource containing valuable elements such as carbon and phosphorus which can be recovered using thermochemical conversion and utilized for the chemical industry. The biogenic origin of carbon offers a renewable and sustainable alternative to fossil-based raw materials contributing to resource circularity and reducing the dependency on primary feedstocks. This study investigates the thermochemical carbon conversion and phosphorus release behavior from SS and sewage sludge coke (SSC) with a focus on determining the kinetics of the carbon conversion as well as the phosphorus release. The experiments were conducted using a thermogravimetric analysis under controlled gasification conditions with varying temperatures up to 1450°C, different heating rates (HRs) of 2.5 K min-1 to 15 K min-1 and gasification atmosphere compositions with different partial pressures of carbon dioxide in argon.Both, the isothermal and non-isothermal method have been used to assess the carbon conversion and were compared with each other. The energies of activation were 175 kJ mol-1 and 162 kJ mol-1 for a pCO2 of 1 bar with a reaction order of 0.68 ± 0.12. Three particle evolution models (VM, RPM and SCM) were implemented and compared. A novel method was used to determine the starting temperature of the phosphorus release (1015°C in nitrogen). Based on the peak positions of the phosphorus signal, the kinetic parameters (EA = 359 kJ mol-1 and k0 = 1.5 · 109 s-1) for the phosphorus release were determined.These results provide new insights into the phosphorus release kinetics and contribute to the understanding required for process design and phosphorus recovery from SS.